Establishment of a Human Multiple Myeloma Xenograft Model in the Chicken to Study Tumor Growth, Invasion and Angiogenesis - Martowicz, Agnieszka (J Vis Exp, 2015)
Multiple myeloma (MM), a malignant plasma cell disease, remains incurable and novel drugs are required to improve the prognosis of patients. Due to the lack of the bone microenvironment and auto/paracrine growth factors human MM cells are difficult to cultivate. Therefore, there is an urgent need to establish proper in vitro and in vivo culture systems to study the action of novel therapeutics on human MM cells. Here we present a model to grow human multiple myeloma cells in a complex 3D environment in vitro and in vivo. MM cell lines OPM-2 and RPMI-8226 were transfected to express the transgene GFP and were cultivated in the presence of human mesenchymal cells and collagen type-I matrix as three-dimensional spheroids. In addition, spheroids were grafted on the chorioallantoic membrane (CAM) of chicken embryos and tumor growth was monitored by stereo fluorescence microscopy. Both models allow the study of novel therapeutic drugs in a complex 3D environment and the quantification of the tumor cell mass after homogenization of grafts in a transgene-specific GFP-ELISA. Moreover, angiogenic responses of the host and invasion of tumor cells into the subjacent host tissue can be monitored daily by a stereo microscope and analyzed by immunohistochemical staining against human tumor cells (Ki-67, CD138, Vimentin) or host mural cells covering blood vessels (desmin/ASMA). In conclusion, the onplant system allows studying MM cell growth and angiogenesis in a complex 3D environment and enables screening for novel therapeutic compounds targeting survival and proliferation of MM cells.